How to play the triangle game. Issue 550 (3rd February 2017) - Crilly, Tony
Abstract : We are given n sticks of lengths 1, 2, 3, …, n and three are selected at random. Which selections enable a triangle to be formed? This question can be written in the form of a game: you win if a triangle can be formed from the three numbers interpreted as side lengths, you lose if they do not. We let ℕ n = {1, 2, 3, …, n }, and see there are two variants of the game: From ℕ n draw at random three numbers sequentially. At each stage do not replace the drawn number. From ℕ n a number is drawn at random and is recorded. In three stages three numbers are drawn. Replace the number at each stage.